Gitelman Syndrome in Post-Partum Pre-Eclampsia in Dr. Soetomo Hospital, Surabaya, Indonesia - Erix Agus Hasudungan Telaumbanua; Ferdy Royland Marpaung (Indian Journal of Forensic Medicine & Toxicology, 2021)
Gitelman Syndrome (GS) is an autosomal recessive tubular kidney disorder. The disorder is rare with a prevalence estimated to be 1 in 40,000 individuals. We closely observed a 28-year-old female with complaints of stiffness and cramps on both hands and feet for 2 weeks and became worse in 3 days before admittance, nausea (+), vomiting (+), shortness of breath (+). Medical records showed that patient underwent post SC 32nd day because of severe pre-eclampsia + IUGR + Oligohydramnion. Physical examination showed GCS 456, blood pressure 140/80 mmHg, heart rate 96x/minute, respiration rate 24x/minute, temperature 37 oC. Laboratory results showed Hb 9.4 g/dl, MCV 86.8 fL, MCH 29.6 pg, MCHC 34.1 g/dL, WBC 7.83x103/uL, PLT 483x103/uL, potassium 2.8 mmol/L, sodium 138 mmol/L, chloride 95 mmol/L, calcium 8.3 mg/dL, magnesium 1.1 mg/dL, phosphate 3 mg/dL, BUN 8 mg/dL, serum creatinin 0.76 mg/dL, urinary calcium 488.4 mg/24 hours, urinary creatinine 488.4 mg/24 hours, proteinuria +1, and blood gas test suggested mixed metabolic alkalosis and respiratory acidosis. Gitelman Syndrome is characterized by hypokalemia, hypomagnesemia, metabolic alkalosis and hypocalciuria. The diagnosis of GS is generally relatively late because of its difficulty to be clinically categorized; therefore, a more comprehensive diagnosis approach is needed. The diagnosis of Gitelman Syndrome is based on clinical symptoms and laboratorial abnormalities and can be confirmed by genetic testing.